Hair As a Barrier to Physical Activity among African American Women: A Qualitative Exploration - Joseph, Rodney P.; Coe, Kathryn; Ainsworth, Barbara E.; Hooker, Steven P.; Mathis, LaTanya; Keller, Colleen (Frontiers in Public Health, 2018)
Background. African American (AA) women face unique sociocultural barriers to physical activity (PA) engagement. Such barriers may contribute to their low PA levels and high cardiometabolic disease burden. One particular barrier reported among AA women in recent research is that being physically active can have an undesirable effect on the hairstyles and hair maintenance of many AA women. However, the underlying mechanisms contributing to this barrier have not been fully elucidated. The purpose of this study was to explore hairstyle maintenance as a barrier to PA among AA women and identify effective strategies to overcome this barrier in the design of a culturally relevant PA intervention. Methods. A qualitative study design was used. Data were collected from focus groups conducted with 23 sedentary and obese AA women (M age = 38.1 years, M BMI = 39.8 kg.m2). Content analysis was used to analyze these focus group data. Results. Three key themes emerged from the qualitative narratives of participants: 1) Impact of Perspiration on Hair and Hairstyle Maintenance, 2) Image and Social Comparisons, and, 3) Solutions to Overcome Hair-related Barriers to PA. For Impact of Perspiration and Hairstyle Maintenance, participants described how perspiring while engaging in PA negatively impacts many of their hairstyles. Participants further discussed how time and monetary burdens associated with PA-related hairstyle maintenance further contributed to this issue. Findings for the theme of Image and Social Comparison focused on how an AA woman’s hairstyle is an important part of the image and the social comparisons made by non-AAs regarding the hairstyles and maintenance practices of AA women. For Solutions to Hairstyle Maintenance Barriers, participant described a variety of potential styling techniques that may help alleviate PA-related maintenance concerns, including braids, locks, and natural hairstyles. However, no styling technique was uniformly endorsed by all study participants. Conclusions. Findings highlight the significance of hair in the AA community and provide further insight on appropriate intervention design strategies to overcome this sociocultural barrier to PA. Future research is needed to corroborate and further expand on our findings.